PENERIMAAN KONSUMEN AKAN MINUMAN SARI BUAH JERUK LOKAL DI BATU-JAWA TIMUR - Lyli Mufidah; Trifena Honestin; Zainuri Hanif (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
The Consumer Acceptance of Local Citrus Drink in Batu-East Java Fruit juice products in Indonesia are still dependent on imported raw materials. This situation needs to be our concern, considering that Indonesian citrus have many varieties and qualities that are not inferior to imported fruit. Therefore, a study was conducted on consumer acceptance of local citrus juice produced in Indonesian Citrus and Subtropical Fruits Research Institute (ICSFRI) using raw materials of four local mandarin varieties, namely Satsuma, Batu 55, JRM and Terigas. Eighty-seven respondents participated in this survey that held in July 2019. Product satisfaction and performance were analyzed using the CSI and IPA methods. Respondent consumptions patterns were also seen to find out the initial description of the quantity and benefit that were sought by consumers of citrus drinks. The results showed that the most preferred processed products from citrus were drinks, with consumption pattern of 1-2 times (37,9%) and 3-4 times (31%) each month. Here, health becomes the main reason for consuming this product. From the analysis, it is illustrated that all respondents received well the three local citrus juice (Terigas, Satsuma, JRM) products, where quality improvement still needs to be done. Citrus varieties that become the main recommendation is Terigas citrus because it’s fulfilled three main citrus juice attributes (citrus flavor, aroma and color) and have the highest customer satisfaction value. This is also supported by the higher vitamin C content, which is needed to increase body immunity, especially in this pandemic era. Keywords: customer satisfaction index (CSI), fruit juice, local citrus, index performance analysis (IPA), vitamin CABSTRAKProduk sari buah di Indonesia masih menggantungkan bahan baku produknya dari buah impor. Hal ini menjadi perhatian, mengingat jeruk Indonesia memiliki beragam varietas dan kualitas yang tidak kalah dengan buah impor. Oleh karena itu dilakukan studi terhadap penerimaan konsumen akan minuman sari buah jeruk lokal yang diproduksi di Balai Penelitian Tanaman Jeruk dan Buah Subtopika (Balitjestro) dengan menggunakan bahan baku empat varietas jeruk keprok lokal, yakni jeruk Satsuma, Batu 55, JRM dan Terigas. Delapan puluh tujuh responden berpartisipasi dalam survei yang diadakan bulan Juli 2019. Kepuasan dan kinerja produk dianalisis menggunakan metode CSI dan IPA. Pola konsumsi responden juga dilihat untuk mengetahui gambaran awal kuantitas dan manfaat yang dicari oleh konsumen minuman sari buah jeruk. Hasil penelitian menunjukkan bahwa produk olahan dari jeruk yang paling disukai adalah minuman, dengan pola konsumsi 1-2 kali (37,9%) dan 3-4 kali (31%) setiap bulannya serta kesehatan sebagai alasan utama dalam mengkonsumsi produk ini. Dari analisis tergambar bahwa keseluruhan responden menerima dengan baik tiga produk sari buah jeruk lokal, dimana peningkatan kualitas masih perlu dilakukan. Varietas jeruk yang menjadi rekomendasi utama adalah jeruk Terigas, karena telah memenuhi tiga atribut utama (rasa jeruk, aroma, dan warna) serta memiliki nilai kepuasan konsumen paling tinggi. Hal ini juga ditunjang dengan kandungan vitamin C yang lebih tinggi untuk meningkatkan imunitas tubuh, terutama di era pandemi ini.Kata kunci: customer satisfaction index (CSI), index performance analysis (IPA), jeruk lokal, sari buah, vitamin C